Efecto de tres niveles de lisina líquida, sobre la performance de pollos de la línea COBB - 500 en la etapa de inicio en Yurimaguas - Ramos Meza, Ellieth (2019)
During the development of the research work, the objective was to evaluate the effect of three levels of liquid lysine on the performance of Cobb 500 line chickens in the initiation stage in Yurimaguas. Using 96 1-day-old Cobb 500 chickens, where they were distributed in 4 experimental treatments and 4 repetitions, a completely randomized design (DCA) with a degree of reliability (P<0.05) was used. The parameters evaluated were: feed intake, weight gain, feed conversion ratio, mortality and economic merit. The treatments were made up of: T0 (control treatment); T1 (0.90% liquid lysine), T2 (1.0% liquid lysine) and T3 (1.10% liquid lysine). The values obtained for food consumption in T3 were 1083.25 g followed by T2, T1 and T0 which were 1060.56, 1057.32 and 1030.71 g, respectively and showing no significant statistical difference between treatments (P<0.05). In terms of weight increase, T3 achieved a higher value with 570.94 g, followed by T2 with 520.89 g., T1 with 491 g and T0 with 438.99 g. and finding significant statistical difference (P>0.05) between the treatments. On the other hand, the feed conversion ratio obtained: 2.84; 2.75; 2.68 and 2.55 for T0, T1, T2 and T3 respectively and no significant statistical difference was found between treatments (P<0.05). No mortality occurred during the investigation. The greatest economic gain was achieved in Q4, with a better profitability of S/ 1.02.